Globalization and the Strategy of Iran - Tanha, Azam Yousefi (International Journal of Bio-resource and Stress Management, 2011)
Internationalization of the economy and complex technological programs has directed the industrial communities to an ideal purpose that finally appears in globalization project with some sense and interpretations. The evolution waves deducted from globalization stream have imposed a heavy dominance on world. This progress has faced by many developing or undeveloped countries with serious challenges. The decision making about joining to this stream is one of the biggest challenges. Different nations in the world have special geographical positions, natural resources, particularly energy, accessibility to seas, oceans, vicinity to big powers and therefore have their own role in international system or affecting the fields and international relations in any way. In particular, due to their important view point of big power of world, they will fall in a positive or negative interaction in regional and global arena. In this new contest period, Iran not only is an exempt, but by having so much of above factors, is laid in the heart of middle-east that is a region full of political, military, economic and cultural events, and always has been noteworthy for world power. Now middle-east is the arena for global competitions that the smallest event in this area will have great world reflex and interventions from regional and ultra regional nations. Now this region is a testing place for big powers for leadership of the world, because the economic pulse is beating here. In this research it was tried to investigate this situation using dispassionate positions and an academic view, and in respect to that Iran is not a member of globalization and World Trading Organization (WTO).